Settlement Disputes in Banceuy Traditional Village: Perspective of Customary Law and Islamic Law - Kusmayanti, Hazar; Kania, Dede (Magister Kenotariatan, Universitas Jambi, 2024)
In the realm of marriage, the indigenous community residing in the Banceuy Traditional Village still conducts Sundanese traditional ceremonies, despite marriages being conducted under Islamic law.There are times when the married life of these indigenous people experiences prolonged disputes. This research aims to examine the settlement of marital disputes in the Banceuy traditional village from the perspective of customary law and Islamic law. The approach method used in this research is normative juridical research. The research specifications used are descriptive analytical, namely by providing data or a description as accurately as possible regarding the object of the problem. Based on the research, it is concluded that the dispute resolution that is often adopted in the community order of Banceuy Traditional Village is known as babadan tenan. Dispute resolution by babadan tenan, in which the parties to the dispute will appoint traditional elders and/or hamlet heads to mediate disputes in a marriage relationship in the customary jurisdiction of Banceuy Traditional Village. Of course, this peaceful dispute resolution is known in Islamic law because Islamic law teaches the use of peacemakers similar to the practice of mediation in the Indonesian legal system.